Discovery of a novel 2-aminopyrazine-3-carboxamide as a potent and selective inhibitor of Activin Receptor-Like Kinase-2 (ALK2) for the treatment of fibrodysplasia ossificans progressiva. (15th May 2022) - Ullrich, Thomas; Arista, Luca; Weiler, Sven; Teixeira-Fouchard, Sylvie; Broennimann, Valérie; Stiefl, Nikolaus; Head, Victoria; Kramer, Ina; Guth, Sabine
Graphical abstract: Abstract: Inhibition of mutant activin A type-1 receptor ACVR1 (ALK2) signaling by small-molecule drugs is a promising therapeutic approach to treat fibrodysplasia ossificans progressiva (FOP), an ultra-rare disease leading to progressive soft tissue heterotopic ossification with no curative treatment available to date. Here, we describe the synthesis and in vitro characterization of a novel series of 2-aminopyrazine-3-carboxamides that led to the discovery of Compound 23 showing excellent biochemical and cellular potency, selectivity over other BMP and TGFβ signaling receptor kinases, and a favorable in vitro ADME profile.